Writing for animation - Beaumont, Laura, 1956-; Larson, Paul, (Screenwriter) (London, England : Zed Books, 2021)
"Animation is one of the fastest growing mediums in the film and television world - whether it's Frozen or Paw Patrol, Family Guy or Rick and Morty. This book is the definitive guide to storytelling for writers, directors, storyboard artists and animators. Suitable for both the student and the professional, it provides indispensable knowledge on the entire process of writing for animated movies, TV series and short films. The reader will be provided with all the tools necessary to produce professional quality scripts that will start, or further, their career in animation. Beginning with the fundamentals of 'why animation?' this book will lead the reader through a series of principles that will raise the level of their storytelling. Many people are trying to break into the world of writing for animation and a lot of the people who are 'already in' would like to get more work. The reality is that writing for animation is a very specific craft that can be learnt like any other craft. This book will give the reader both the basic and advanced techniques that will put them ahead of the rest of the field. These principles are tried and tested on a daily basis by the authors, who have over three hundred screen credits to their name, including six animated features"--
-- 1. Let's Get Going! -- 2. All about Goals -- 3. The Three Act Structure -- 4. Emotion -- 5. Jeopardy -- 6. Creating Characters -- 7. Finding the Funny -- 8. Dialogue Workshop -- 9. Understanding your Technology -- 10. Directing on the Page -- 11. Specifics of Writing for Children -- 12. Writing for an Existing Show -- 13. Writing the Movie -- 14. Creating a Show that Works -- 15. Collaboration -- 16. The Pitch -- 17. Four Top Tips Bibliography Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Animated films -- Authorship; Animated television programs -- Authorship; Animated films; Electronic books